The Role of Research in Revitalizing Rural Areas: Global and Chinese Perspectives - Fan, Shenggen (2018)
Shenggen Fan International Mega Programme – Lessons to Learn, Chinese Academy of Agricultural Sciences (CAAS) June 25, 2018